Corporate Social Responsibility and Customer Loyalty: A Review of Literature - Mberewere, Simbai; Kudzanai, Matowanyika; Tinashe, Ruvinga (CV. Literasi Indonesia, 2024)
Corporate social responsibility takes an increasingly important role for businesses and receives the attention of many people. The relationship between corporate social responsibility and customer loyalty has been tested in many business fields however little has been done to support the effect of CSR on customer loyalty. So, the study aims to highlight the influence of corporate social responsibility on customer loyalty in emerging economies such as Zimbabwe. To achieve this objective, the study uses literature on corporate social responsibility and customer loyalty from various scholarly databases. The document analysis method was one of the primary methods of investigation used in this study. It featured a methodical approach to doing a literature review, wherein pertinent materials were sourced from academic sources like Scopus, Google Scholar, Web of Science and the Directory of Open Access The majority of the journals that were used in the review of literature were mostly open access DOAJ indexed directories. Drawing on Carroll's CSR theory, the present research develops the underlying mechanism through which corporate social responsibility influences customer loyalty by simultaneously including corporate reputation, customer satisfaction, and customer loyalty. The findings demonstrate that corporate social responsibility initiatives are significantly and positively associated with corporate reputation, customer satisfaction, and customer trust. Moreover, the results reveal that corporate reputation, customer trust, and customer satisfaction have mediated the relationship between corporate social responsibility and customer loyalty. The study recommends that companies increase their CSR spending to achieve word-of-mouth referrals, favorable customer image, and overall gain a competitive advantage.